Inherited thrombophilia and venous thromboembolism: testing rules in clinical practice - I. V. Zotova; D. A. Zateyshchikov (Российский кардиологический журнал, 2020)
Testing for inherited thrombophilia in patients with venous thromboembolism is one of the most common genetic testing options prescribed by clinicians. Despite the large evidence base for the relationship of hereditary hemostasis disorders with the risk of venous thrombosis, most patients should not be tested. Performing tests in the acute phase of thrombosis or during anticoagulant therapy leads to erroneous results. The choice of anticoagulant therapy regimen and its duration are not specified by the presence of hereditary thrombophilia. The test results can be useful for increasing medication adherence of patient, determining the cause of thrombosis, especially at a young age or in atypical localization.